Kryptogenní fibrotizující alveolitida - Svobodová, L; Homolka, J (Casopis lekaru ceskych, 2007)
Presented article deals with the pathogenesis of cryptogenic fibrotizing alveolitis (CFA), gives distinct histological types according ATS and ERS, considers clinical CFA picture and recommends examination program for this disease. The anti-inflammatory and immunosuppressive treatment is discussed together with other therapeutic approaches (long-lasting oxygenotherapy at home, transplantation and treatment of pulmonary hypertension). Final part deals with less frequent clinical manifestations.
Keywords: plicní fibróza; lidé; Pulmonary Fibrosis; Humans